Potential Impacts of Agriculture on Nepal Birds - Inskipp, C.; Baral, H.S. (Our Nature, 2011)
This paper is a review of the potential impacts of agriculture on Nepal birds. It includes an overview of agriculture in Nepal and the changes that have taken place between the early 1950s and 2007. Agricultural development has been sluggish, and has failed to keep pace with population growth. In recent years the yields of major food crops in Nepal have been lower than other South Asian countries and Nepal is now dependent on food imports. Land holding size per family and field sizes have both decreased markedly during the period. If hill regions are considered independently, all cereal crops yields have stagnated in the last 30 years and gains in production that have been made, have been due to increases in area of cultivation, at the expense of natural habitats: forests, wetlands and grasslands. Crop productivity in the hills has declined due to land degradation. Of the 28% of Nepal land that is degraded, 10% is poorly managed sloping agriculture terraces. As yields and production of cereal crops have fallen, many farmers have shifted to growing cash crops, to meet the demands of the increasing urban population and encouraged by government agricultural policies. Cultivation area, production and yields of some cash crops have significantly increased since 1964/65. Nepal’s livestock population is one of the highest in Asia and nearly every rural household keeps domestic animals resulting in widespread and serious problems of livestock overgrazing. The importance of agricultural habitats for Nepal birds is reviewed: 21% of bird species recorded in Nepal utilizes agricultural habitats for foraging at some season. The many ecological benefits of birds to agriculture and the damage caused by birds to agriculture are described: the former far outweigh the latter. Changes in agricultural practices (including changes in crops and crop production, impacts of livestock overgrazing) are having major and far-reaching impacts on natural habitats - grasslands wetlands and forests and their bird species; these changes and impacts are detailed and analysed. The increasing use of pesticides in Nepal, which is especially high on vegetable cash crops, the serious impacts of pesticides on birds and the environment and alternatives to pesticides are reviewed. Fertilizer use in Nepal and the damaging impacts of fertilizer over-use on birds and the environment are also reviewed. Recommendations to improve farming methods for the benefit of the environment are given. These include government measures to promote organic agriculture; government measures to expand the System of Rice Intensification and to encourage further use of Effective Microorganisms, both of which have significant benefits for environment, birds and farmers; field surveys to monitor bird populations and bird distribution on agricultural lands, and outreach and awareness-raising for farmers to apply best practice for sustainable environmentally friendly farming. DOI: 10.3126/on.v8i1.4339